Additive manufacturing of NiTi shape memory alloys using pre-mixed powders - Tor, Shu Beng (2019)
This work presents a comparative study on the in-situ alloying of NiTi shape memory alloys (SMAs) by directed energy deposition (DED), selective laser melting (SLM) and selective electron beam melting (SEBM) processes using pre-mixed Ni-Ti powders. The influence of process parameters on the microstructural homogeneity, phase formation and thermomechanical properties of NiTi alloy has been systematically studied. DED could build solid NiTi alloys with good interlayer fusion and phase transformation characteristics. However, a substantial amount of uniformly dispersed Ti2Ni intermetallics can embrittle this material. SLM-built NiTi parts show a tradeoff between microstructural inhomogeneity and keyhole defects when the energy densities are varied. In addition, the strong exothermic reaction in Ni-Ti powder mixtures during printing can disturb the melt pool, making it challenging to elaborate this material and obtain desired phases by using SLM. Moreover, SEBM is found to be unsuitable to in-situ synthesize this highly reactive material due to the lack-of-fusion vs. powder-ignition dilemma in the mandatory preheating step. It is suggested to adopt DED to in-situ alloy NiTi parts when using the elementally blended powders as feedstocks.